2016
DOI: 10.1007/s00784-016-1877-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of double antibiotic and calcium hydroxide pastes on dislodgement resistance of an epoxy resin-based and two calcium silicate-based root canal sealers

Abstract: There is a little information about the influence of antibiotic medicaments on the bond strength of root canal sealer. These findings suggest that the use of DAP does not affect the adhesion strength of AH Plus, MTA Fillapex, and Total Fill BC Sealers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
4
19
1
1
Order By: Relevance
“…The shear bond test could separately investigate a bond between sealer to dentin or sealer to GP/CSGP. Even the methods of the 2 bond tests are different; the result in our study was in accordance with those obtained from push‐out bond strength studies, which reported that the bond of CSS was superior or similar to AH sealer . In contrast, other studies reported the lower bond strength of CSS compared with AH sealer .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The shear bond test could separately investigate a bond between sealer to dentin or sealer to GP/CSGP. Even the methods of the 2 bond tests are different; the result in our study was in accordance with those obtained from push‐out bond strength studies, which reported that the bond of CSS was superior or similar to AH sealer . In contrast, other studies reported the lower bond strength of CSS compared with AH sealer .…”
Section: Discussionsupporting
confidence: 89%
“…Even the methods of the 2 bond tests are different; the result in our study was in accordance with those obtained from push-out bond strength studies, which reported that the bond of CSS was superior or similar to AH sealer. 4,21,[23][24][25] In contrast, other studies reported the lower bond strength of CSS compared with AH sealer. 20,22,26,27 The difference in experimental conditions, such as irrigants, wetness of canal or obturation technique, might have caused the discrepancies in results among these studies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…12 Yapılan çalışmalarda, kanal içinde arta kalan medikamanın kanal patının dentin tübüllerine penetrasyonunu engellediği, kanal dolgusunun kök dentinine bağlantısını azalttığı bildirilmiştir. [13][14][15] Ayrıca; kalsiyum hidroksit, İAP ve ÜAP'nin klinik konsantrasyonlarının deri altı dokularda orta derecede inflamatuar reaksiyona yol açtığı ve insan diş pulpa kök hücrelerinde sitotoksik olduğu bildirilmiştir. 16,17 Araştırmacılar arasında kanal içi ilaçların kanalın daimi dolgusundan önce tamamen uzaklaştırılması konusunda görüş birliği bulunmaktadır.…”
unclassified